2019
DOI: 10.3390/ani9060302
|View full text |Cite
|
Sign up to set email alerts
|

Amino Acids Influencing Intestinal Development and Health of the Piglets

Abstract: The amino acids and other components of diet provide nourishment for piglet intestinal development and maturation. However, early-weaned piglets struggle with tremendous stress, impairing normal intestinal health and leading to intestinal dysfunction and even death. The high prevalence worldwide of post-weaning diarrhoea syndrome (PWDS) in piglets has led to much interest in understanding the important role of nutrients in the establishment and maintenance of a functional intestinal tract. In particular, the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 84 publications
0
24
0
1
Order By: Relevance
“…In the present study, the increases in the SCFA concentrations and their receptor ( GPR41 ) in the MFGM group, as well as the promoted propionate metabolism profiles, indicated that administrating MFGM in the first week regulated the microbiota and SCFA metabolism, which eventually energized the enterocytes and enhanced the gut barrier functions ( Kelly et al., 2015 ). In addition, the modification in biosynthesis and metabolism of some amino acids, such as phenylalanine, tyrosine and tryptophan in the MFGM group were also reported to contribute to intestinal integrity and health ( Mou et al., 2019 ). Besides, the increased pantothenate and CoA biosynthesis profiles may accelerate energy production, contributing to the intestinal homeostasis and growth development ( Grevengoed et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the increases in the SCFA concentrations and their receptor ( GPR41 ) in the MFGM group, as well as the promoted propionate metabolism profiles, indicated that administrating MFGM in the first week regulated the microbiota and SCFA metabolism, which eventually energized the enterocytes and enhanced the gut barrier functions ( Kelly et al., 2015 ). In addition, the modification in biosynthesis and metabolism of some amino acids, such as phenylalanine, tyrosine and tryptophan in the MFGM group were also reported to contribute to intestinal integrity and health ( Mou et al., 2019 ). Besides, the increased pantothenate and CoA biosynthesis profiles may accelerate energy production, contributing to the intestinal homeostasis and growth development ( Grevengoed et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Trp is known to be involved in several physiological functions (Le Floc'h et al, 2011). It plays a central role in protein synthesis because it is the main protein component of the piglet's body (Mou, Yang, Yin, & Huang, 2019. Moreover, Trp is also the precursor for the synthesis of pituitary 5-HT, which regulates several processes, such as voluntary feed intake (Höglund et al, 2019;Martin, Osadchiy, Kalani, & Mayer, 2018), mood (Quintero-Villegas & Valdés-Ferrer, 2020;Martin, Osadchiy, Kalani, & Mayer, 2016), and social and physiology behaviors (Poletto, Kretzer, & Hötzel, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Las poliaminas se sintetizan a partir de ornitina, arginina y metionina (Pegg 2008;Gao et al 2013). Sin embargo, arginina es un aminoácido limitante durante la lactancia debido a su baja disponibilidad en leche (Wu et al 2004;Mou et al 2019). La enzima ASS cataliza la síntesis de arginina a partir de citrulina; por tanto, esta enzima desempeña un papel importante en la síntesis de poliaminas tanto en lactancia como durante los primeros días postdestete puesto que ayuda a corregir la deficiencia de arginina en leche (Wu et al 2018).…”
Section: Discussionunclassified